Engineering constructed of high selectivity dexamethasone aptamer based on truncation and mutation technology - Qin, Yadi; Qin, Yanan; Bubiajiaer, Hayilati; Chen, Fengxia; Yao, Jun; Zhang, Minwei (Frontiers in Bioengineering and Biotechnology, 2022)
Various biosensors based on aptamers are currently the most popular rapid detection approaches, but the performance of these sensors is closely related to the affinity of aptamers. In this work, a strategy for constructed high-affinity aptamer was proposed. By truncating the bases flanking the 59 nt dexamethasones (DEX) original aptamer sequence to improve the sensitivity of the aptamer to DEX, and then base mutation was introduced to further improve the sensitivity and selectivity of aptamers. Finally, the 33 nt aptamer Apt-M13 with G-quadruplex structures was obtained. The dissociation constant (Kd) was determined to be 200 nM by Graphene oxide (GO)-based fluorometry. As-prepared Apt-M13 was used for a label-free colorimetric aptamer sensor based on gold nanoparticles, the LOD was 3.2-fold lower than the original aptamer described in previous works. The anti-interference ability of DEX analogs is also further improved. It indicates that truncation technology effectively improves the specificity of the aptamer to DEX in this work, and the introduction of mutation further improves the affinity and selectivity of the aptamer to DEX. Therefore, the proposed aptamer optimization method is also expected to become a general strategy for various aptamer sequences.